Hematology, Cytochemistry and Ultrastructure of Blood Cells in Asiatic Black Bear (Ursus thibetanus) - Chaleow Salakij; Jarernsak Salakij; Nual-Anong Narkkong; Ludda Trongwonsa; Rattapan Pattanarangsan (Agriculture and Natural Resources, 2005)
Blood cells from adult Asiatic black bear (Ursus thibetanus) were examined and measured after stainning with modified Wright stain and cytochemical stains, including Sudan Black B (SBB), Periodic acid Schiff’s reaction (PAS), a-naphthyl acetate esterase (ANAE), acid phospatase (AcP) and bglucuronidase (b-glu). Red blood cells were uniform in shape, with 7.3 mm mean diameter in size and easy to form rouleaux. Using scanning electron microscopic (SEM) examinations revealed normal and abnormal red blood cell surfaces. Neutrophils contained several vacuoles as detected by light microscope and revealed themselves as large granules under transmission electron microscope. Neutrophils stained strongly positive with SBB, ANAE; weak positive with PAS and negative with AcP and b-glu. Using SEM, neutrophil surfaces revealed several microvilli and some micropores. Eosinophils contained numerous small round red refractive granules with some vacuoles. Eosinophils stained strongly positive with SBB and ANAE but negative with PAS and b-glu. Basophils had variable numbers of intense basophilic granules that obscured the very long lobulated nucleus. Basophils stained moderately positive with SBB but strongly positive with ANAE. Lymphocytes were negative with SBB but have 3 patterns of reactivity with ANAE, AcP and b-glu, including negative, focal dot and fine granular stainings. Monocytes stained moderately with SBB and moderately to strongly with for ANAE and b-glu. The SEM examinations could differentiate white blood cells by their surface contours. Transmission electron microscopic examinations revealed organelles within all blood cells.